Brunetti's chisels in anterior and posterior rachiotomy. Issue 3 (14th October 2019) - Boscolo‐Berto, Rafael; Emmi, Aron; Macchi, Veronica; Stecco, Carla; Loukas, Marios; Tubbs, R. Shane; Porzionato, Andrea; De Caro, Raffaele
Abstract : Rachiotomy entails vertebral surgical incision, generally followed by exposure of the spinal cord, and is performed primarily for educational, research, or medicolegal purposes. Over time, several tools have been developed for this procedure, but Lodovico Brunetti designed the first effective prototypes in the mid‐nineteenth century. To show the technical details of and the necessary maneuvers to be performed for Brunetti's rachiotomies to succeed, a computer‐aided systematic literature review of online databases was performed to identify publications concerning Brunetti's chisels used for rachiotomy. Additional references from the studies and treatises included held in the Historical Section of the Medical Library at the University of Padova were checked manually for pertinent information. The known variants of Brunetti's chisels were reported in detail from the first to the third versions produced and intended for both posterior (first and third prototypes) and anterior (second prototype) vertebral dissection. Further evolution that led to the current commercialized model devoted to posterior use also was described. The models' strengths and weaknesses were assessed, as well as the nature of the changes Brunetti introduced over time and their motivation. In conclusion, these tools could represent an alternative to the use of electric saws, particularly for dissectors who prefer to have greater manual control in incising the vertebrae. Clin. Anat. 33:355–364, 2020. © 2019 Wiley Periodicals, Inc.